The SwAD-Task – An Innovative Paradigm for Measuring Costs of Switching Between Different Attentional Demands - Liebherr, Magnus; Antons, Stephanie; Brand, Matthias (Frontiers in Psychology, 2019)
Task switching paradigms are frequently used to identify costs of switching between modalities, spatiality, attributes, rules, etc., but switching between different attentional demands has been somehow neglected. The present study introduces an innovative paradigm, that allows to test single attentional demands (such as selective and divided attention), but rather the process of switching between these demands. We examined the feasibility of the paradigm by focusing on the demands of selective and divided attention with a sample of 94 people (age: M=21.44 years, SD=2.68; 76 women). In addition, we tested correlations between the implemented single attentional demands and commonly used measures of selective and divided attention. Results show no general differences between individual trials under single demand conditions. Reaction times under divided attention are significantly higher compared to selective attention. In the switching condition, reaction times in both demands increase with increased switching. Furthermore, switching costs significantly increase in selective but not in divided attention. Means of selective and divided attention in both single and switching conditions significantly correlate with a commonly used measure of selective attention. Means of divided attention under single demand significantly correlate with performance in a commonly used dual-task paradigm. Summarizing the present findings, it can be stated that the introduced paradigm comprises a feasible way for quantifying the process of switching attention between different demands.